Reduction–rebridging strategy for the preparation of ADPN-based antibody–drug conjugates12. Issue 5 (20th April 2018) - Koniev, Oleksandr; Dovgan, Igor; Renoux, Brigitte; Ehkirch, Anthony; Eberova, Jitka; Cianférani, Sarah; Kolodych, Sergii; Papot, Sébastien; Wagner, Alain
Abstract : The reduction–rebridging strategy is a powerful method for the preparation of stable and homogeneous antibody–drug conjugates (ADCs). Abstract : The reduction–rebridging strategy is a powerful method for the preparation of stable and homogeneous antibody–drug conjugates (ADCs). In this communication, we describe the development of the arylene-dipropiolonitrile (ADPN) functional group for the rebridging of reduced disulphide bonds and its application in the preparation of potent and selective ADCs.